HUBUNGAN STATUS GIZI GENGAN TINGKAT KEBUGARAN JASMANI SISWA PUTRA KELAS X MA NW KALIJAGA TAHUN 2018 - munipiddin, Munipiddin -; Tamim, Muhammad Husni; Nopiana, Rina - (Universitas Hamzanwadi, 2018)
The porpose of this research was to find out the correlation between status nutrition and level of body vitality on tenth grade MN NW Kalijaga in school year 2018. This research was descriptive qualitative design with correlation research. The population of this research was all of male students of MA NW Kalijaga. Technique collecting data was done by weighing body weight and measuringbody high to determine students? nutrition and tes kebugaran jasmani indonesian(TKJI) data analysis used formula of product moment correlation. Result of hypothesis show that t-hitung>t-table was (0,414>0,312) it means that Ho rejected and Ha accepted. It can conclude that there are correlation between students? nutrition and level of body vitality of male students on tenth gread of MA NW Kalijaga in school year 2018